Pelvic floor muscle training associated with the use of pessaries in the treatment of pelvic organ prolapse: Scope review protocol (Research, Society and Development, 2024)
The present study is a scoping review protocol that aims to map the scientific evidence regarding the training of pelvic floor muscles associated with the use of pessaries in the treatment of symptomatic pelvic organ prolapse in adult women, in any health institution. It will be based on the guidelines of the Preferred Reporting Items for Systematic and Meta-Analyses – Extension for Scoping Reviews (PRISMA – ScR), taking into account the methodology of the Joanna Briggs JBI Institute for scope reviews and guided by the question of review in terms of the model conceptual: Population, Concept and Context (PCC). The search for articles will be carried out in databases and scientific information portals, namely: PubMed Central (PMC), Sportdiscus, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Embase, Web of Science, Virtual Library Regional Portal in Health (VHL), Pubmed of the National Library of Medicine (NLM), Scopus and PEDro. All identified records will be grouped and loaded into the Rayyan® software. Data will be extracted from the articles included in the scoping review by two independent reviewers, using a data extraction tool developed by the reviewers. A narrative summary will accompany the tabulated and/or graphical results and describe how the results are related to the review objective and question.